PUBLIC RELATIONS IN INDIA - A STUDY OF POWER SECTOR - Kumar, Dr. R. Ravi (Journal of Advanced Research in Journalism & Mass Communication, 2021)
Public relations is a distinctive management function which helps establish and maintain mutual lines of communication, understanding, acceptance and cooperation between an organization and its publics; involves the management of problems or issues; helps management to keep informed and responsive to public opinion; defines and emphasizes the responsibility of management to serve the public interest; helps management to keeps abreast of and effectively utilize change, serving as an early warning system to anticipate trends; and uses research and sound and ethical communication techniques as its principal tools. In this context this study tries to explore two-fold path. The first attempts to understand the way Public Relations and Corporate Communication departments are structured in organizations and the functions they perform in meeting the challenges of contingent environments. The second focuses on the management induced constraints, if any, experienced by Public Relations or Corporate Communication personnel. Core focus area of this study is: To broadly explore the organizational environments then summarize discuss and conclude the Public Relations/Corporate Communication departments of large power industries. How to cite this article: Kumar RR. Public Relations in India - A Study of Power Sector. J Adv Res Jrnl Mass Comm 2020;7(3): 1-5.